2023
DOI: 10.1002/ldr.4675
|View full text |Cite
|
Sign up to set email alerts
|

Decoupling and partitioning the effect of climate and afforestation on long‐term vegetation greening in China since the 1990s

Abstract: Vegetation is an essential component of the Earth's surface system, and is a clear indicator to global climate changes. Understanding the long-term characteristics of vegetation variations and their relationship to climate and human activities is important for regional sustainable development and ecological construction. In this study the ensemble empirical mode decomposition, the breaks for additive seasonal and trend algorithm and trend analysis were applied to obtain the spatiotemporal characteristics of th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 77 publications
0
4
0
Order By: Relevance
“…More systematic and comprehensive quantitative analyses are needed for the hydrothermal limitation as well as its spatio-temporal patterns during recent decades. Secondly, human activities also have critical influences on the spatio-temporal patterns of NPP (Gang et al, 2018; Peng et al, 2023; Yang et al, 2021), but these lack indepth analysis in our study. Thirdly, we only used the mean annual NPP from previous studies to validate the simulations in this study.…”
Section: Discussionmentioning
confidence: 85%
See 2 more Smart Citations
“…More systematic and comprehensive quantitative analyses are needed for the hydrothermal limitation as well as its spatio-temporal patterns during recent decades. Secondly, human activities also have critical influences on the spatio-temporal patterns of NPP (Gang et al, 2018; Peng et al, 2023; Yang et al, 2021), but these lack indepth analysis in our study. Thirdly, we only used the mean annual NPP from previous studies to validate the simulations in this study.…”
Section: Discussionmentioning
confidence: 85%
“…In addition, the elevations of NPP from the HRB to the WRB, and then the LYRB (Figures 2, 4, 8–10) imply a decrease of hydrothermal limitation of vegetation along the climate gradients. Previous studies also concluded an increasing trend of vegetation productivity from northwest to southeast of China, along with the increase of temperature and precipitation (e.g., Peng et al, 2023; Piao et al, 2005). Lower NPP in the HRB is primarily due to that the widespread insufficiency of hydrothermal condition for vegetation growth (Gao et al, 2016; Liu et al, 2017), which is confirmed by the greater importance of temperature and precipitation to the spatial pattern of NPP in the HRB (Figure 3a).…”
Section: Discussionmentioning
confidence: 88%
See 1 more Smart Citation
“…It is derived from the National Earth System Science Data Center (http://www.geodata.cn) during 1990–2018, with a spatial resolution of 5 km. This data set has been widely used to investigate the changes in vegetation growth and productivity in diverse ecoregions globally (Chen, Wang, et al, 2022; Peng et al, 2023). Based on the vegetation NDVI dataset, we implement seasonal and trend decomposition using Loess (STL, see the supplementary materials online for the method) decomposition to split the time‐series data in each grid into an overall trend, a repeating annual cycle, and a residual component (Okedi & Fisher, 2021; Scotch et al, 2021); and we use the residual component in our resilience analysis.…”
Section: Study Area and Materialsmentioning
confidence: 99%